2024
DOI: 10.1002/bit.28646
|View full text |Cite
|
Sign up to set email alerts
|

Cell culture product quality attribute prediction using convolutional neural networks and Raman spectroscopy

Hamid Khodabandehlou,
Mohammad Rashedi,
Tony Wang
et al.

Abstract: Advanced process control in the biopharmaceutical industry often lacks real‐time measurements due to resource constraints. Raman spectroscopy and Partial Least Squares (PLS) models are often used to monitor bioprocess cultures in real‐time. In spite of the ease of training, the accuracy of the PLS model is impacted if it is not used to predict quality attributes for the cell lines it is trained on. To address this issue, a deep convolutional neural network (CNN) is proposed for offline modeling of metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Thus, the need to downsample the Raman features while preserving their statistical attributes becomes imperative. In our previous research (Khodabandehlou et al, 2023), it was demonstrated that downsampling a Raman signal by a factor of 10 preserves its statistical properties. This suggests that downsampling by a factor of less than 10 can also maintain these properties.…”
Section: Downsamplingmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the need to downsample the Raman features while preserving their statistical attributes becomes imperative. In our previous research (Khodabandehlou et al, 2023), it was demonstrated that downsampling a Raman signal by a factor of 10 preserves its statistical properties. This suggests that downsampling by a factor of less than 10 can also maintain these properties.…”
Section: Downsamplingmentioning
confidence: 99%
“…A Raman baseline correction technique was proposed by Eilers and Boelens utilizing asymmetric least square smoothing (Eilers & Boelens, 2005). In this technique, the baseline of the Raman spectra is calculated as follows (Khodabandehlou et al, 2023):…”
Section: Baseline Correctionmentioning
confidence: 99%
See 3 more Smart Citations